The Effectiveness of Trans-Electrical Nerve Stimulation (TENS) in Reducing Pain Caused by Orthodontic Movement; A Randomized Controlled Trial - Haider Zahid, Ulfat Bashir Raja, Owais Khalid Durrani, Sofia Shehzad, Maria Aslam, Mahnoor Khan, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To check the effectiveness of TENS therapy in reducing pain caused by orthodontic movement. Methods: This was a single-blinded parallel-arm randomized controlled trial among patients presented for treatment of increased overjet using the split-mouth technique. Ethical consent was obtained from 45 patients. An initial levelling and alignment of dentition were achieved, followed by extraction of maxillary pre-molars, and canines were distalized, maintaining 100grams of force. The TENS pads were placed on the cheeks. One side was supplied with active impulses, considered an interventional side, while the other was not supplied with impulses and was marked as the control side. Pain intensity was measured on the tested tool (NRS scale) during resting and clenching (T1). The patient was instructed to use the device the same way for a total of five more times, at T2 (2hrs), T3 (6hrs), T4 (24hrs), T5 (48hrs), and T6 (72hrs). The data were analyzed using SPSS version 24, Chi-square test was applied to compare the pain intensity. Results: Among 45 patients (77.8% female and 21.2% male), the mean age of 19.0 ± 4.13 years. The average pain intensity on rest at 0 and 2 hours was 1.33 ± 1.108, which was at peak T3 (6 hours) 1.87 ± 1.546 and T4 (24 hours) 1.71 ± 1.359. However, it significantly decreased at T5 (48 hours) and T6 (72 hours) of intervention, which were 1.38 ± 0.8 and 1.31 ± 1.04, respectively. This difference was statistically significant (p<0.05). The same pattern of pain reduction was seen in patients with clenching (p<0.05). This showed that the pain intensity was decreased, but the pattern was not linear, as indicated that the pain at T3 and T4 was increased, but later, it was significantly decreased at T5 and T6. A negative correlation was observed between pain intensity and interval of TENS applied onward from the 4th interval in both groups (TENS applied on rest and TENS applied on clenching). Pain score at 72 hours was significantly low compared to post TENS applied (p<0.001). Conclusion: TENS efficacy is insignificant at T1 and T2, with a significant increase in pain during T3 and T4; however, at T5 and T6, there was a significant reduction in pain which indicates a greater efficacy of the device reducing pain compared to the placebo.